KEANEKARAGAMAN BIVALVIA DI PESISIR PANTAI PAYUMB KELURAHAN SAMKAI DISTRIK MERAUKE - Lely Kustiyarini; Irba Djaja (AGRICOLA, 2011)
Bivalves is one class of the phylum Mollusca and is one of the non-living resources of fish that have high diversity. Research on "Diversity bivalves coastal area Payumb in village Samkai Merauke District "from June until  July 2011. This research aim to determine the species diversity of coastal area bivalves Payumb Village Samkai Merauke District. Sampling was taken from three observation stations and each station have been seven replications. The method used is descriptive method. Measurement of physical-chemical parameters of waters carried out directly in the field. Parameters measured include temperature, salinity, pH and substrate type. The results show as many as 10 species of bivalves, consisting of, 8 families, 4 orders, 1 class and a phylum is Anadara granosa, Anomala, Atrina serrata, Mactra janeiroensis, Mactra sp, Meretrix lusoria, Modiolus philippinarum, Polymesoda expansa, Sanguinolaria nuttali, Solen grandis. The value of diversity index (H') bivalves 0.29 to 0.47, the evenness index (e) bivalves 0.56 to 0.97, and bivalves dominance index value 0.46 to 0.52. Physico-chemical quality of coastal waters Payumb have a value that is still relatively normal. Water temperature 26-28 ° C, salinity 26-27% o, pH 6.6, and the type of substrate is a substrate of mud and sandy mud.